Enhancing English Language Capacity for Staff in an Environmental Education Center through a Structured Training Program - Nurwahida Nurwahida; Thamrin Tahir; Muhammad Ilyas Thamrin Tahir; Rahmiati Rahmiati; Mursidin Yusuf (PT. Global Research Collaboration, 2025)
English language proficiency is a strategic requirement for environmental education-based institutions such as the Puntondo Environmental Education Center (PPLH) in Takalar, South Sulawesi, which actively interacts with international tourists and researchers from around the world. The English Language Training Program for PPLH Puntondo staff is designed to improve cross-language communication skills, strengthen service professionalism, and expand the reach of environmental knowledge dissemination. This article aims to describe the implementation process, achievements, and impact of the training on participants. The program lasted for three months (July–September 2025) with 24 face-to-face sessions and a practice-based, participatory approach. Results showed significant improvements in self-confidence, speaking skills, and mastery of environmental thematic vocabulary. This program has proven effective in building staff communicative competence and provides a sustainable learning model that can be replicated by other environmental institutions.